A STUDY ON CHARACTER IDENTITY HIGHLIGHTS WITH REFERENCE TO INDIAN MYTHOLOGICAL CHARACTER: MAHISHASUR - Guha, Shreejit; Semwal, Varuna; Chakrabarti, Debkumar (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The mainstream media popularizes norms established by the dominant culture while the alternate media highlights the other representations. To assess how designers perceive character highlights in overlapping but distinct cultures in mainstream and alternate media, reference can be taken of the state-of-art representation of the body of the mythical Hindu demon king Mahishasur, presented as an evil force in Durga Puja festivities in West Bengal, India and the newly constructed visual representation of Mahishasur as the martyr “Hudur Durga” in the Santhali culture prevalent in the state. Through discussions with idol-makers from Kumartuli, the hub of idol-making in West Bengal about the perception of Mahishasur in mainstream representation and interactions with the Santhal community in Ayodhya hills, Purulia about the current perception in the Santhali culture, this study sought to understand the varying perceptions around the character representation of the mythical character leading to the development of counter-culture character designs and the possibility of acceptance of such alternate representations among the dominant culture populace.